Presbyopia and its anatomical and physiological variants - Gupta, M; Sukul, RR; Gupta, Y; Dey, M; Phougat, A; Bhardwaj, U; Dixit, S (Nepalese Journal of Ophthalmology, 2011)
Aim: To study the various ocular anatomical and physiological parameters in presbyopia. Materials and methods: We studied the various ocular anatomical and physiological parameters like corneal curvature (keratometry readings: K1 and K2), central corneal thickness (CCT), anterior chamber depth (ACD), lens thickness (LT) and axial length (AL) in 100 presbyopic patients between 35 - 55 years of age. The patients were divided into two age groups: I (35 – 44 years) and II (45-55 yrs). ACD, AL and LT were measured using an Ascan. CCT was measured with ultrasonic pachymetry. Results: The CCT decreased (BE), LT increased and ACD decreased (RE) significantly with increasing age (p < 0.05). There was no significant difference in males and females. Nearly 3/4th of the total increase in lens thickness was responsible for the decrease in the anterior chamber depth and the rest, 1/4th , goes posteriorly. Corneal curvature and AL showed no significant change with age. Conclusions: The mean of CCT decreased significantly with advancing age. As age increased, the mean value of lens thickness increased and anterior chamber depth decreased. Nearly 3/ 4th of total increase in LT was anteriorly, decreasing the ACD. Corneal curvature and AL has no relation with age. Key words: Presbyopia, central corneal thickness, anterior chamber depth, lens thickness, axial length DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5269 Nepal J Ophthalmol 2011; 3(2): 155-158